S-Glutathionylation-Controlled Apoptosis of Lung Epithelial Cells; Potential Implications for Lung Fibrosis - Elizabeth Corteselli; Reem Aboushousha; Yvonne Janssen-Heininger (MDPI AG, 2022)
Glutathione (GSH), a major antioxidant in mammalian cells, regulates several vital cellular processes, such as nutrient metabolism, protein synthesis, and immune responses. In addition to its role in antioxidant defense, GSH controls biological processes through its conjugation to reactive protein cysteines in a post-translational modification known as protein S-glutathionylation (PSSG). PSSG has recently been implicated in the pathogenesis of multiple diseases including idiopathic pulmonary fibrosis (IPF). Hallmarks of IPF include repeated injury to the alveolar epithelium with aberrant tissue repair, epithelial cell apoptosis and fibroblast resistance to apoptosis, and the accumulation of extracellular matrix and distortion of normal lung architecture. Several studies have linked oxidative stress and PSSG to the development and progression of IPF. Additionally, it has been suggested that the loss of epithelial cell homeostasis and increased apoptosis, accompanied by the release of various metabolites, creates a vicious cycle that aggravates disease progression. In this short review, we highlight some recent studies that link PSSG to epithelial cell apoptosis and highlight the potential implication of metabolites secreted by apoptotic cells.